Motivasi Penonton Livestream di Aplikasi Twitch - Azel Ryhan; D. Nawolo Baskoro (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2021)
The study focuses on finding motivation for others to watch people play video games on Twitch. The population studied is between the ages of 16 and 24 in Bekasi (509,407 People). Samples were randomly extracted with a Slovin formula with 400 responses. This data is retrieved using Google Form and analyzed using Warpls. Research motivation is the perspective of Uses and Gratification: Cognitive, Affective, Personal integration, Social integration and Tension release. The results is that cognitive factors have a significant impact on the Streamers Watch (H1c β = 0,051), Personal Integrative, Social Integrative, and Tension Release Factor have a very influence by Hours Watching variables(H3a β = 0,068; H4a β = 0,065; H5a β = 0,067), The tension release factor is strongly influenced by the streamers follow variable(H5c β = 0,093) and there are no factors that really affect the Subscribe variable